2020
DOI: 10.5415/apallergy.2020.10.e25
|View full text |Cite
|
Sign up to set email alerts
|

Importance of microbial extracellular vesicle in the pathogenesis of asthma and chronic obstructive pulmonary disease and its diagnostic potential

Abstract: There are rising evidences of the human microbiome as a potentially influential player that is actively engaged in shaping the pathogenetic processes and other unresolved issues both in asthma and other chronic respiratory diseases, particularly of the airways. The biological components such as microbiome in inhaled air can induce immune dysfunction and inflammation, leading to inflammatory pulmonary disorders such as asthma and chronic obstructive pulmonary disease (COPD). Microbe-derived extracellular vesicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…The results obtained in the current study are in accordance with those of Mueller et al [66] who evidenced that endotoxin aggregates (macromolecules) showed much higher biological activity than monomers. More recently, Yang et al [67,68] and Kim et al [69] highlighted the significance of extracellular bacterial vesicles (EV), mostly those containing LPS, as potential causative factors of pulmonary inflammation, thus confirming the views published about 20 years earlier by the authors of the presented study. Yang et al [68] expressed an opinion that EVs, especially Gram-negative outer membrane vesicles (OMVs), induce Th17 immune response and lead to neutrophilic inflammation which may contribute to the development of asthma, emphysema, COPD, and lung cancer.…”
Section: Hypersensitivity Pneumonitis (Hp)supporting
confidence: 87%
“…The results obtained in the current study are in accordance with those of Mueller et al [66] who evidenced that endotoxin aggregates (macromolecules) showed much higher biological activity than monomers. More recently, Yang et al [67,68] and Kim et al [69] highlighted the significance of extracellular bacterial vesicles (EV), mostly those containing LPS, as potential causative factors of pulmonary inflammation, thus confirming the views published about 20 years earlier by the authors of the presented study. Yang et al [68] expressed an opinion that EVs, especially Gram-negative outer membrane vesicles (OMVs), induce Th17 immune response and lead to neutrophilic inflammation which may contribute to the development of asthma, emphysema, COPD, and lung cancer.…”
Section: Hypersensitivity Pneumonitis (Hp)supporting
confidence: 87%
“…In bacteria, extracellular vesicles range from 20 to 400 nm in diameter and they have been involved in bacterial functions such as biofilm formation, competition, antibiotic resistance or horizontal gene transfer (106). Extracellular vesicles of bacterial origin are not only involved in bacteria-bacteria communication, but also in bacteria-host cell communication, being able to elicit phenotypic changes in host cells altering their function with both detrimental and beneficial actions (107)(108)(109). Characterization studies of their cargo showed that they can contain several types of molecules, including structural and soluble proteins such as enzymes, secondary metabolites, virulence factors, glycolipids, lipopolysaccharides, bacterial antigens and a wide range of nucleic acids, including DNA and microRNA-like molecules, which have been extensively summarized in other reviews (110)(111)(112).…”
Section: Involvement Of Gut Microbiota In Release Of Plant Mirnas From Extracellular Vesiclesmentioning
confidence: 99%
“…They, therefore, demonstrated the important role of the microbiome as a potential diagnostic marker of asthma, employing the serum. Kim et al [ 140 ] focused their attention on bacterial EVs IgG antibody titers in serum, observing that in asthma and COPD patients, these titers were higher than in healthy controls, postulating that these values could be used as a diagnostic tool for lung disease.…”
Section: Exosomes In Biofluids In Asthmatic Inflammationmentioning
confidence: 99%